Penyuluhan Masyarakat Pesisir Ma’rang Melalui Pemanfaatan Hasil Ikan Sebagai Kerupuk - Mukhlishah, Nurul; Herawaty, Herawaty; Mahi, Faizah Mahi; Asjulia, Asjulia; Kurnia, Akhmad Kurnia (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
The importance of community empowerment in processing marine products, especially fish, which can be made into high-value economic products such as fish crackers. Ma'rang Village has the potential for abundant fish resources, but there is still limited community knowledge about efficient processing techniques. The purpose of this counseling is to provide understanding to the community on how to make quality fish crackers, as well as their benefits as a business opportunity. The method used was a direct counseling approach by providing materials on fish cracker making, involving local residents as participants. The counseling also included techniques for selecting fish raw materials, processing, and proper storage so that the product remains durable and has a high selling value. The results of the counseling showed that the community was enthusiastic and began to understand the process of making fish crackers with the right techniques, as well as the importance of maintaining product quality. In addition, they also gained insight into the utilization of social media to expand the market. The implication of this activity is the improvement of community skills in processing fish into processed products with economic value, as well as opening opportunities for them to develop a more competitive fish cracker business. It is hoped that this activity can continue with the provision of further training related to marketing and access to more modern production equipment to increase the competitiveness of fish cracker products in local and national markets.